2013
DOI: 10.3390/su5041387
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of Scope, Type and Temporality in Mustang, Nepal. Opportunities for Adaptation in a Farming System Facing Climatic and Market Uncertainty

Abstract: Climate change is projected to increase the seasonality in river flows in the great river systems of Himalaya and impose challenges to regional food production. Since climate change increases the uncertainty in local weather patterns, people's ability to maintain local agricultural production will probably depend on how flexible the local farming systems are to adjust to unpredictable changes. The objective of this paper is to investigate the flexibility of one such farming system which is located in Mustang, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The water storage function of glaciers and heavy snowfall is diminishing, leading to more seasonal flash flooding and an increase in erosion and landslides. These changes in climatic factors are consistent with those found in other mountain areas of Nepal by various studies (Manandhar et al 2011;Chhetri et al 2012;Holmelin and Aase 2013;Aryal et al 2016;Pradhan et al 2015).…”
Section: Discussion and Future Directionssupporting
confidence: 91%
See 1 more Smart Citation
“…The water storage function of glaciers and heavy snowfall is diminishing, leading to more seasonal flash flooding and an increase in erosion and landslides. These changes in climatic factors are consistent with those found in other mountain areas of Nepal by various studies (Manandhar et al 2011;Chhetri et al 2012;Holmelin and Aase 2013;Aryal et al 2016;Pradhan et al 2015).…”
Section: Discussion and Future Directionssupporting
confidence: 91%
“…Many studies of local perceptions of climate change and its impacts, the vulnerability of people to these changes, and their adaptations have recently been published (e.g. Macchi et al 2011;Manandhar et al 2011;Chhetri et al 2012;Gentle and Maraseni 2012;Shrestha et al 2012;Baul et al 2013;Kusters and Wangdi 2013;Holmelin and Aase 2013;Aryal et al 2016;Pradhan et al 2015;Wang et al 2016). These studies found that households perceived changes in climate and reported the increased incidence of climate related hazards such as floods, droughts, landslides, livestock diseases, crop pests, erratic rainfall and temperature extremes.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptation to climate change in the context of development has been much discussed in recent years, with the discourse focussing primarily on whether adaptation is part and parcel of the development process in developing countries (IPCC 2001;Adger et al 2003;Holmelin & Aase 2013). It has been argued that it is impossible to separate adaptation from development (Cannon & Muüller-Mahn 2010).…”
Section: Climate Change Adaptation In Context Of Development and Ruramentioning
confidence: 99%
“…The National Gene Bank is primarily responsible for the conservation of unique accession on long-term basis, as base collections for posterity, predominantly in the form of seed 15 . 16 . But such NTFPs have to tackle other situations also.…”
Section: Government Initiatives For Preservation Of Medicinal Plantsmentioning
confidence: 99%
“…The rising temperature and changing patterns of precipitation, combined with high and volatile food prices in international markets, these small scale farmers get bound to adapt new practices. Defining this 'flexibility' as 'uncommitted potential for change', Homelin & Aase 16 , have argues that farming system flexibility may be analysed in terms of the three aspects: flexibility of scope, flexibility of type and temporal flexibility.…”
Section: Government Initiatives For Preservation Of Medicinal Plantsmentioning
confidence: 99%